Analysis of injuries and medical check for all Japan Junior Tennis Championships in Japan - Fujisawa, A.; Okudaira, S.; Ohta, K.; Umebayashi, K.; Miyama, T.; Yonetani, Y.; Beppu, M.; Nakata, K.; Kawai, Y.; Yamasaki, Y. (Medicine and Science in Tennis, 2009)
Introduction Nation-wide top junior tennis players under 18 participate in All Japan Junior Tennis Championships in the mid-summer days which the temperature goes above 35°C. It is critical to prevent from serious hyperthermia and other sports-related injures. The purposes of this study were to investigate the incidence and type of injuries during tournament and to evaluate the significance of the self-medical check which had been introduced since 2007. Materials and methods Every player was advised to submit the self-medical check(SMC) sheet which consists of two parts; a past history of illness and 14 questions about the present health status. All SMC sheets were reviewed. Every injury was recorded and analyzed for the incidence and the type of injuries. Results In 2007, 1652 players participated in this tournament. There were 39 injuries which required medical time-out among 700 matches. The incidence of injury was 5.6%. Nineteen (48.7%) were musclo-skeletal injuries and four (10.3%) were skin troubles. There were five (12.8%) hyperthermia and three needed to call an ambulance to treat in a buck-up hospital. The SMC sheet was collected for 710 players and submission rate was 43.0%. The number of players who assessed themselves as abnormal in more than three questions was 73 (10.3%). Exhaustion, lack of sleep, and fatigue were most common abnormalities in self assessment. Summary 1) The incidence of injury was 5.6% in All Japan Junior Tennis Championships in 2007. Musco-skeletal injuries, skin troubles, and hyperthermia occurred in 48.7%, 10.3%, and 12.8%, respectively. Three were serious hyperthermia. 2) Self medical check (SMC) had the significance in some extent for the junior players, their families and coaches to educate and become aware of the importance of self assessment, although the submission rate was 43.0% in the first year.